Expression of Toll-Like Receptors 2 and 4 and Related Cytokines in Patients with Hepatic Cystic and Alveolar Echinococcosis. (9th November 2015) - Tuxun, Tuerhongjiang; Ma, Hai-Zhang; Apaer, Shadike; Zhang, Heng; Aierken, Amina; Li, Yu-Peng; Lin, Ren-Yong; Zhao, Jin-Ming; Zhang, Jin-Hui; Wen, Hao
Abstract : Several studies have demonstrated the important role of Toll-like receptors in various parasitic infections. This study aims to explore expression of Toll-like receptors (TLRs) and related cytokines in patients with human cystic echinococcosis (CE) and alveolar echinococcosis (AE). 78 subjects including AE group (N = 28 ), CE group (N = 22 ), and healthy controls (HC, N = 28 ) were enrolled in this study. The mRNA expression levels of TLR2 and TLR4 in blood and hepatic tissue and plasma levels related cytokines were detected by using ELISA. Median levels of TLR2 mRNA in AE and CE groups were significantly elevated as compared with that in healthy control group. Median levels of TLR4 expression were increased in AE and CE. Plasma concentration levels of IL-5, IL-6, and IL-10 were slightly increased in AE and CE groups compared with those in HC group with no statistical differences (p > 0.05 ). The IL-23 concentration levels were significantly higher in AE and CE groups than that in HC subjects with statistical significance. The increased expression of TLR2 and IL-23 might play a potential role in modulating tissue infiltrative growth of the parasite and its persistence in the human host.